Solar-Powered Highschool Library Information System Design and Implementation - Lestari, Putri Yuni; Triawan, Farid; Lestari, Tika Endah; Harjon, Aditiya; Belfaqih, Idrus Husin; Djajasoepena, Rafie; Ramadhan, Ammar; Wandy, Wandy (Center for Research and Community Service of Sampoerna University, 2022)
A school library is important in education, especially in high schools to support day-to-day operations. The purpose of this community service is to develop and install a solar-powered Library Information System for the State Highschool No. 6 Cirebon (SMA Negeri 6 Cirebon), Indonesia, in which the existing library operations were done manually. First, for the library database server, a small-size Raspberry Pi is utilized with a SLiMS library automation system installed and run over the school’s local network. Then, a sufficient energy resource is required to run the computer system; in this case, to support running the Raspberry Pi device. For this, a solar panel set-up is installed at the school to generate the electric power as the renewable energy resouce. Packages of solar panels with the battery are easily found in the online Indonesian marketplace, and this made the implementation of solar energy could become faster. In addition, a series of academic seminars is also held to support the library system operation as well as the school teachers.